RESEARCH METHODOLOGY PRACTICAL LABS AND GUIDES - RODZALAN, SHAZAITUL AZREEN; ABDULLAH, NOR HAZANA; ABDUL HAMID , NOR AZIATI (Penerbit UTHM, 2024)
Research Methodology: Practical Labs and Guides is a thorough guide designed to lead researchers through every phase of the research process, whether using quantitative or qualitative methods. It provides hands-on lab sheets and instructions for each research step, ensuring that researchers are well-equipped to plan, execute, and report their studies successfully. The book begins by introducing fundamental research concepts and differentiating between quantitative and qualitative methodologies, setting a strong foundation for the research journey. The book will guiding researchers on selecting a research topic and effectively searching for relevant literature using Mendeley software. Next, the section on formulating a problem statement helps researchers refine and clarify their research problem, creating a clear focus for their inquiry. This book also includes labs on developing a literature review matrix (LR Matrix) to synthesize existing research, formulate focused research questions, and conceptualize and operationalize variables. In addition, it covers labs on designing surveys and interviews, as well as collecting data. Once data is collected, the book provides labs on analyzing and interpreting both quantitative and qualitative data. Finally, the section on reporting offers advice on effectively communicating research findings, including the appropriate structure and style for research reports.